Value orientations and social cohesion in organizational discourses: a civil-society perspective - Rico Neumann; Barbara Pfetsch; Swen Hutter; Simon Koschut; David Schieferdecker; Jule Specht (Information, Communication & Society, 2025)
Against the backdrop of political polarization and societal fragmentation, liberal democracy, more than ever, rests on social cohesion. Civil-society organizations (CSOs) are pivotal in fostering this cohesion by building social capital and serving as catalysts of social change. However, civil society is also a space of ambivalence where conflicting values and priorities are negotiated and, at times, contested. Integrating insights from social psychology, political sociology, and communication scholarship, this study seeks to better understand the extent and ways in which values are articulated in the external communication of CSOs, and how these values are linked to their public claims of fostering social cohesion. Combining organizational survey data of nearly 800 CSOs in Germany with a content analysis of their websites, this study finds clear tendencies toward communitarian (vs. individualistic), postmaterialist (vs. materialist), and secular-rational (vs. traditional) values in the CSOs' self-portrayals. CSOs that view themselves as agents of social change and, to some degree, politically active CSOs tend to invoke values more often, while those focused on sports/leisure and cultural activities were least likely to do so. Finally, for articulating organizational visions of socially cohesive communities, it does not matter much which value orientations in particular are invoked by CSOs as long as values are present in their external communication.
Keywords: 300; Civil-society organizations (CSOs); organizational communication; social cohesion; values